Dental trauma and mouthguard usage among ice hockey players in Turkey premier league - KARGÜL, BETÜL (BLACKWELL MUNKSGAARD, 2005)
An epidemiological survey was carried out among the ice hockey players of Turkish Premier Ice Hockey League. The purpose of the present study was to evaluate the prevalence of dental trauma in youth and adult ice hockey players, as well as to check if the players were aware of mouthguards and had used any. The players were interviewed to determine the occurrence of dental trauma during ice hockey and mouthguard usage level. Results revealed that awareness of Turkish ice hockey players to dental trauma is neglected while the majority of players also demonstrated limited utilization of mouthguard.
Keywords: mouthguard; dental trauma; ice hockey; epidemiological survey; Turkey; INJURIES; SPORTS; CHILDREN